Adhesive composition, adhesive film, laminate and method for manufacturing circuit connection structure
The adhesive composition, featuring a radical polymerizable compound, a radical polymerization initiator, and an epoxy-containing acrylic resin, addresses the insufficient half-cut properties of conventional adhesive films, resulting in improved peeling reliability and circuit connection performance.
Patent Information
- Application Number
- JP2023150864
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-19
- Publication Date
- 2025-04-01
AI Technical Summary
Conventional circuit connection adhesive films do not have sufficient half-cut properties, leading to reconnection issues when only one adhesive film is used after half-cutting.
An adhesive composition containing a radical polymerizable compound, a radical polymerization initiator, and an acrylic resin with at least one epoxy group, which forms an adhesive film with improved half-cut properties.
The adhesive film exhibits excellent half-cut properties, allowing for reliable peeling and reducing the likelihood of reconnection, while also providing high adhesive strength and low connection resistance in circuit connections.
Smart Images

Figure 2025043533000004 
Figure 2025043533000005 
Figure 2025043533000006
Abstract
Description
[Technical field]
[0001] The present disclosure relates to methods for producing adhesive compositions, adhesive films, laminates, and circuit connection structures. [Background technology]
[0002] Conventionally, various adhesive materials have been used to connect circuits. For example, an adhesive film (film-like adhesive) for circuit connection having anisotropic conductivity in which conductive particles are dispersed in the adhesive is used as an adhesive material for connecting a liquid crystal display and a tape carrier package (TCP), connecting a flexible printed circuit board (FPC) and a TCP, or connecting an FPC and a printed wiring board (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] WO 2005 / 54388 Summary of the Invention [Problem to be solved by the invention]
[0004] In general, an adhesive film for circuit connection is placed on a substrate and cut into a tape shape for use. In this case, a technique called "half cut" is sometimes used in which only the adhesive film for circuit connection is cut and the substrate itself is not cut. However, conventional adhesive films for circuit connection do not have sufficient half cut properties. That is, in conventional adhesive films for circuit connection, when only one side of the adhesive film cut by half cut is used, the adhesive film may reattach at the cut surface, and the other adhesive film may also be peeled off at the same time, even though only one side of the adhesive film needs to be peeled off.
[0005] Therefore, some aspects of the present disclosure aim to provide an adhesive film with excellent half-cut properties, an adhesive composition capable of forming the adhesive film, a laminate comprising the adhesive film on a substrate, and a method for producing a circuit connection structure using the laminate. [Means for solving the problem]
[0006] Some aspects of the present disclosure provide the following [1] to
[10] .
[0007] [1] An adhesive composition comprising a radically polymerizable compound, a radical polymerization initiator, and an acrylic resin having at least one epoxy group in the molecule and a weight average molecular weight of 5,000 or more.
[0008] [2] The adhesive composition according to [1], wherein the content of the acrylic resin is 1 to 15 mass % based on the total amount of solids contained in the adhesive composition.
[0009] [3] The adhesive composition according to [1] or [2], wherein the acrylic resin has an epoxy equivalent of 1,000 or less.
[0010] [4] The adhesive composition according to any one of [1] to [3], wherein the radically polymerizable compound includes a (meth)acrylate compound having at least one phosphate group in the molecule.
[0011] [5] The adhesive composition according to any one of [1] to [4], further comprising at least one thermoplastic resin selected from the group consisting of a phenoxy resin, a polyester resin, a polyurethane resin, a polyester urethane resin, a butyral resin, an acrylic resin, and a polyimide resin.
[0012] [6] The adhesive composition according to any one of [1] to [5], further comprising conductive particles.
[0013] [7] An adhesive film comprising a first adhesive layer made of the adhesive composition according to any one of [1] to [6].
[0014] [8] The adhesive film described in [7], further comprising a second adhesive layer laminated on the first adhesive layer, wherein at least one of the first adhesive layer and the second adhesive layer contains conductive particles.
[0015] [9] A laminate comprising a substrate and the adhesive film according to [7] or [8] provided on the substrate.
[0016]
[10] A method for manufacturing a circuit connection structure, comprising: a half-cutting process of cutting the adhesive film of the laminate described in [9] along an outline line forming the outline of an adhesive film piece; a process of peeling the adhesive film piece formed by the half-cutting process from the base material; and a process of interposing the adhesive film piece between a first circuit member having a first electrode and a second circuit member having a second electrode, and thermocompressing the first circuit member and the second circuit member to electrically connect the first electrode and the second electrode to each other. Effect of the Invention
[0017] According to some aspects of the present disclosure, it is possible to provide an adhesive film having excellent half-cut properties, an adhesive composition capable of forming the adhesive film, a laminate having the adhesive film on a substrate, and a method for producing a circuit connection structure using the laminate. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a cross-sectional view showing an adhesive film according to one embodiment of the present disclosure. [Diagram 2] FIG. 2 is a perspective view illustrating a manufacturing process of a circuit connection structure according to one embodiment of the present disclosure. [Diagram 3] FIG. 3 is a cross-sectional view illustrating a manufacturing process of a circuit connection structure according to one embodiment of the present disclosure. [Figure 4] FIG. 4 is a schematic diagram for explaining a method for evaluating the half-cut property. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, the embodiments of the present disclosure will be described in detail with reference to the drawings in some cases. In this specification, a numerical range indicated using "~" indicates a range including the numerical values described before and after "~" as the minimum and maximum values, respectively. In addition, the upper limit and lower limit values described individually can be arbitrarily combined. In addition, in this specification, "(meth)acrylate" means at least one of acrylate and the corresponding methacrylate. The same applies to other similar expressions such as "(meth)acryloyl". In addition, "(poly)" means both the case with and without the prefix "poly".
[0020] <Adhesive composition> One embodiment of the present disclosure is an adhesive composition containing a radically polymerizable compound, a radical polymerization initiator, and an acrylic resin having at least one epoxy group in the molecule and a weight average molecular weight of 5000 or more (hereinafter also referred to as an "epoxy group-containing acrylic resin").
[0021] According to the adhesive composition having the above characteristics, an adhesive film having excellent half-cutting properties (i.e., excellent handling properties when peeling off the adhesive film after half-cutting) can be formed. Therefore, it is suitable for use in the production of adhesive films that require half-cutting properties. The reason why such an effect is obtained is not clear, but since the epoxy group-containing acrylic resin tends to have crystallinity, it is presumed that the adhesive composition containing the epoxy group-containing acrylic resin reduces the stress at the time of breaking the adhesive film, thereby obtaining the above effect. In addition, generally, in radical curing adhesives, there are fewer intermolecular bonds formed by the curing reaction compared to non-radical curing adhesives, so that the stress at the time of breaking the adhesive film is likely to be low. Therefore, it is presumed that the adhesive composition being a radical curing system is also one of the reasons why the above effect is obtained.
[0022] Furthermore, the adhesive composition having the above characteristics is suitable for circuit connection, and the adhesive composition makes it possible to easily obtain a circuit connection structure that has sufficiently high adhesive strength and has sufficiently low connection resistance between opposing electrodes.
[0023] The adhesive composition of the present embodiment may be insulating or conductive. That is, the adhesive composition may be used to form an insulating adhesive film, or may be used to form a conductive adhesive film. The conductive adhesive composition may contain conductive particles.
[0024] The adhesive composition of the present embodiment may be used to form an adhesive film consisting of an insulating adhesive layer or a conductive adhesive layer, or may be used to form at least one of the insulating adhesive layer and the conductive adhesive layer of an adhesive film comprising an insulating adhesive layer and a conductive adhesive layer.
[0025] The adhesive composition of the present embodiment may further contain a thermoplastic resin. The epoxy group-containing acrylic resin may be a thermoplastic resin, but even if the epoxy group-containing acrylic resin is a thermoplastic resin, the adhesive composition may further contain a thermoplastic resin other than the epoxy group-containing acrylic resin.
[0026] The components that may be contained in the adhesive composition are described below.
[0027] (Radical polymerizable compound) The radical polymerizable compound is a compound that is polymerized by radicals generated by a radical polymerization initiator, for example. The polymerizable compound may be any one of a monomer, an oligomer, and a polymer.
[0028] The radical polymerizable compound has at least one radical polymerizable group, such as a vinyl group, an allyl group, a styryl group, an alkenyl group, an alkenylene group, a (meth)acryloyl group, or a maleimide group.
[0029] Specific examples of the radical polymerizable compound include (meth)acrylate compounds, maleimide compounds, vinyl ether compounds, allyl compounds, styrene, styrene derivatives, acrylamide derivatives, nadimide derivatives, natural rubber, isoprene rubber, butyl rubber, nitrile rubber, butadiene rubber, styrene-butadiene rubber, acrylonitrile-butadiene rubber, and carboxylated nitrile rubber.
[0030] Examples of (meth)acrylate compounds include epoxy (meth)acrylate, (poly)urethane (meth)acrylate, methyl (meth)acrylate, polyether (meth)acrylate, polyester (meth)acrylate, polybutadiene (meth)acrylate, silicone acrylate, ethyl (meth)acrylate, 2-cyanoethyl (meth)acrylate, 2-(2-ethoxyethoxy)ethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-hexyl (meth)acrylate, and 2-methylethyl (meth)acrylate. Acrylate, 2-hydroxyethyl (meth)acrylate, isopropyl (meth)acrylate, hydroxypropyl (meth)acrylate, isobutyl (meth)acrylate, isobornyl (meth)acrylate, isodecyl (meth)acrylate, isooctyl (meth)acrylate, n-lauryl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, 2-(meth)acryloyloxyethyl phosphate, N,N-dimethyl dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, ethylene glycol diacrylate, diethylene glycol diacrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, polyethylene glycol di(meth)acrylate, polyalkylene glycol di(meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, neo Pentyl glycol di(meth)acrylate, pentaerythritol (meth)acrylate, dipentaerythritol hexa(meth)acrylate, isocyanuric acid modified bifunctional (meth)acrylate, isocyanuric acid modified trifunctional (meth)acrylate, tricyclodecanyl acrylate, dimethylol-tricyclodecane diacrylate, 2-hydroxy-1,3-diacryloxypropane, 2,2-bis[4-(acryloxymethoxy)phenyl]propane, 2,2-bis[4-(acryloxypolyethoxy)phenyl]propane, 2,Examples include 2-di(meth)acryloyloxydiethyl phosphate and 2-(meth)acryloyloxyethyl acid phosphate.
[0031] Examples of the maleimide compound include, in addition to the maleimide compound represented by the above formula (1), 1-methyl-2,4-bismaleimidebenzene, N,N'-m-phenylene bismaleimide, N,N'-p-phenylene bismaleimide, N,N'-m-toluylene bismaleimide, N,N'-4,4-biphenylene bismaleimide, N,N'-4,4-(3,3'-dimethyl-biphenylene) bismaleimide, N,N'-4,4-(3,3'-dimethyldiphenylmethane) bismaleimide, N,N'-4,4-(3,3'-diethyldiphenylmethane) bismaleimide, N,N'-4,4-diphenylmethane bismaleimide, N,N'- Examples of the maleimide include 4,4-diphenylpropane bismaleimide, N,N'-4,4-diphenylether bismaleimide, N,N'-3,3-diphenylsulfone bismaleimide, 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane, 2,2-bis(3-s-butyl-4-8(4-maleimidophenoxy)phenyl)propane, 1,1-bis(4-(4-maleimidophenoxy)phenyl)decane, 4,4'-cyclohexylidene-bis(1-(4maleimidophenoxy)-2-cyclohexyl)benzene, and 2,2'-bis(4-(4-maleimidophenoxy)phenyl)hexafluoropropane.
[0032] Examples of the vinyl ether compound include diethylene glycol divinyl ether, dipropylene glycol divinyl ether, cyclohexane dimethanol divinyl ether, and trimethylolpropane trivinyl ether.
[0033] Examples of the allyl compound include 1,3-diallyl phthalate, 1,2-diallyl phthalate, and triallyl isocyanurate.
[0034] Examples of the styrene derivative include polymerizable compounds in which a hydrogen atom at the α-position or aromatic ring of styrene, such as vinyltoluene and α-methylstyrene, is substituted.
[0035] As the radical polymerizable compound, one kind of compound may be used alone, or multiple kinds of compounds may be used in combination. From the viewpoint of further suppressing peeling under high temperature and high humidity environment and from the viewpoint of obtaining a better resistance value, it is preferable to use a (meth)acrylate compound. By using a (meth)acrylate compound, the balance between the curing reaction speed and the physical properties after curing tends to be excellent.
[0036] The content of the (meth)acrylate compound may be 5% by mass or more, 10% by mass or more, 20% by mass or more, 40% by mass or more, 60% by mass or more, or 80% by mass or more based on the total mass of the radical polymerizable compound, from the viewpoint of further suppressing peeling under a high-temperature and high-humidity environment and from the viewpoint of obtaining a further excellent resistance value. The content of the (meth)acrylate compound may be 100% by mass.
[0037] From the viewpoint of achieving a balance between the crosslink density and cure shrinkage, further reducing the connection resistance, and further improving the connection reliability, it is preferable to use, as the radical polymerizable compound, a compound in which a radical polymerizable group such as a vinyl group, an allyl group, or a (meth)acryloyl group has been introduced into the end or side chain of a thermoplastic resin (thermoplastic polymer) such as an acrylic resin, a phenoxy resin, or a polyurethane resin.
[0038] As a compound having a radical polymerizable group introduced at the end or side chain of a thermoplastic resin, a (poly)urethane (meth)acrylate compound is preferred from the viewpoint of achieving both cohesive strength for reducing connection resistance and elongation for improving adhesive strength, thereby obtaining superior adhesive properties.
[0039] The (poly)urethane (meth)acrylate compound preferably has an alicyclic ring and / or an aromatic ring. Examples of the alicyclic ring that the (poly)urethane (meth)acrylate compound may have include a cyclopentane ring, a cyclohexane ring, a dicyclopentane ring, an adamantane ring, and a norbornane ring. Examples of the aromatic ring that the (poly)urethane (meth)acrylate compound may have include a benzene ring, a naphthalene ring, and a phenanthrene ring.
[0040] The weight average molecular weight of the compound having a radical polymerizable group introduced into the end or side chain of the thermoplastic resin may be 3000 or more, 5000 or more, or 10,000 or more, from the viewpoint of excellent balance between crosslink density and cure shrinkage. The weight average molecular weight of the compound having a radical polymerizable group introduced into the end or side chain of the thermoplastic resin may be 1,000,000 or less, 500,000 or less, or 250,000 or less, from the viewpoint of excellent compatibility with other components (for example, the maleimide compound represented by the above formula (1)). The weight average molecular weight in this specification is a value measured by gel permeation chromatography (GPC) using a calibration curve of standard polystyrene.
[0041] The content of the compound having a radical polymerizable group introduced at the end or side chain of the thermoplastic resin may be 10% by mass or more, 20% by mass or more, or 30% by mass or more based on the total mass of the radical polymerizable compounds, from the viewpoint of further reducing the connection resistance and further improving the connection reliability. The content of the compound having a radical polymerizable group introduced at the end or side chain of the thermoplastic resin may be 90% by mass or less, 80% by mass or less, or 70% by mass or less based on the total mass of the radical polymerizable compounds, from the viewpoint of suppressing the cure shrinkage during polymerization.
[0042] The content of the (poly)urethane (meth)acrylate compound may be 30% by mass or more, 40% by mass or more, or 50% by mass or more based on the total mass of the (meth)acrylate compound from the viewpoint of obtaining further excellent adhesive properties. The content of the (poly)urethane (meth)acrylate compound may be 80% by mass or less, 70% by mass or less, or 60% by mass or less based on the total mass of the (meth)acrylate compound from the viewpoint of improving cohesive force and improving reliability.
[0043] From the viewpoint of improving the cohesive force and further reducing the connection resistance, it is preferable to use a (meth)acrylate compound having a high Tg skeleton (e.g., a (meth)acrylate compound having a tricyclodecane skeleton) as the radical polymerizable compound. From the viewpoint of further reducing the connection resistance, it is preferable that the (meth)acrylate compound having a high Tg skeleton has two methacryloyloxy groups (i.e., is a di(meth)acrylate compound). As such a compound, for example, dicyclopentadiene type diacrylate can be mentioned.
[0044] The content of the (meth)acrylate compound having a high Tg skeleton may be 10% by mass or more, 20% by mass or more, or 30% by mass or more based on the total mass of the (meth)acrylate compounds, from the viewpoint of further improving the cohesive force and further reducing the connection resistance. The content of the (meth)acrylate compound having a high Tg skeleton may be 60% by mass or less, 50% by mass or less, or 40% by mass or less based on the total mass of the (meth)acrylate compounds, from the viewpoint of suppressing the cure shrinkage during polymerization.
[0045] From the viewpoint of further improving the adhesive force to the surface of an inorganic material (metal, etc.) and further improving the adhesive strength between electrodes (for example, between circuit electrodes), it is preferable to use a (meth)acrylate compound having at least one phosphoric acid group in the molecule as the radical polymerizable compound. As the (meth)acrylate compound having at least one phosphoric acid group in the molecule, for example, a (meth)acrylate compound represented by the following formula (1) can be mentioned. [ka]
[0046] In formula (1), n represents an integer of 1 to 3; 1 represents a hydrogen atom or a methyl group.
[0047] The (meth)acrylate compound represented by the above formula (1) can be obtained, for example, by reacting phosphoric anhydride with 2-hydroxyethyl (meth)acrylate. Specific examples of the (meth)acrylate compound represented by the above formula (1) include mono(2-(meth)acryloyloxyethyl)acid phosphate, di(2-(meth)acryloyloxyethyl)acid phosphate, etc.
[0048] The content of the (meth)acrylate compound represented by the above formula (1) may be 0.5% by mass or more, 3% by mass or more, or 5% by mass or more based on the total mass of the (meth)acrylate compound, from the viewpoint of further improving the adhesive force to the surface of an inorganic material (metal, etc.) and further improving the adhesive strength between electrodes (for example, between circuit electrodes).The content of the (meth)acrylate compound represented by the above formula (1) may be 30% by mass or less, 20% by mass or less, or 10% by mass or less based on the total mass of the (meth)acrylate compound, from the viewpoint of pot life.
[0049] The content of the radical polymerizable compound may be 10% by mass or more, 20% by mass or more, or 30% by mass or more based on the total mass of the adhesive composition, from the viewpoint of easily obtaining a crosslink density necessary for reducing the connection resistance and improving the connection reliability. The content of the radical polymerizable compound may be 90% by mass or less, 80% by mass or less, or 70% by mass or less based on the total mass of the adhesive composition, from the viewpoint of suppressing the curing shrinkage during polymerization and obtaining good reliability. From these viewpoints, the content of the radical polymerizable compound may be 10 to 90% by mass, 20 to 80% by mass, or 30 to 70% by mass based on the total mass of the adhesive composition.
[0050] (Radical polymerization initiator) The radical polymerization initiator is a compound that generates radicals by heat, light, or the like. The radical polymerization initiator may be a thermal radical polymerization initiator or a photoradical polymerization initiator, but from the viewpoint of further improving the effect of reducing the connection resistance and achieving superior connection reliability, it is preferable that the radical polymerization initiator is a compound that generates radicals by heat (thermal radical polymerization initiator). As the radical polymerization initiator, one type of compound may be used alone, or multiple types of compounds may be used in combination.
[0051] The thermal radical polymerization initiator decomposes by heat to generate free radicals. That is, the thermal radical polymerization initiator is a compound that generates radicals by applying thermal energy from the outside. The thermal radical polymerization initiator can be arbitrarily selected from conventionally known organic peroxides and azo compounds. As the thermal radical polymerization initiator, from the viewpoint of further improving the flow suppression effect and the peeling suppression effect of the conductive particles, organic peroxides are preferable, and from the viewpoints of stability, reactivity and compatibility, organic peroxides having a one-minute half-life temperature of 90 to 175°C and a weight average molecular weight of 180 to 1000 are more preferable. By having the one-minute half-life temperature in this range, the storage stability is further excellent, the radical polymerizability is sufficiently high, and it can be cured in a short time.
[0052] Specific examples of the thermal radical polymerization initiator include 1,1,3,3-tetramethylbutyl peroxyneodecanoate, di(4-t-butylcyclohexyl) peroxydicarbonate, di(2-ethylhexyl) peroxydicarbonate, cumyl peroxyneodecanoate, dilauroyl peroxide, 1-cyclohexyl-1-methylethyl peroxyneodecanoate, t-hexyl peroxyneodecanoate, t-butyl peroxyneodecanoate, and t-butyl peroxyneodecanoate. Oxypivalate, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, 2,5-dimethyl-2,5-di(2-ethylhexanoylperoxy)hexane, t-hexylperoxy-2-ethylhexanoate, t-butylperoxy-2-ethylhexanoate, t-butylperoxyneoheptanoate, t-amylperoxy-2-ethylhexanoate, di-t-butylperoxyhexahydroterephthalate, t-amylperoxy-3, 5,5-trimethylhexanoate, 3-hydroxy-1,1-dimethylbutyl peroxyneodecanoate, t-amyl peroxyneodecanoate, di(3-methylbenzoyl) peroxide, dibenzoyl peroxide, di(4-methylbenzoyl) peroxide, t-hexylperoxyisopropyl monocarbonate, t-butylperoxymaleic acid, t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxylaurate, 2 organic peroxides such as 5-dimethyl-2,5-di(3-methylbenzoylperoxy)hexane, t-butylperoxy-2-ethylhexyl monocarbonate, t-hexyl peroxybenzoate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, t-butyl peroxybenzoate, dibutyl peroxytrimethyladipate, t-amyl peroxy normal octoate, t-amyl peroxy isononanoate, and t-amyl peroxybenzoate;Examples of azo compounds include 2,2'-azobis-2,4-dimethylvaleronitrile, 1,1'-azobis(1-acetoxy-1-phenylethane), 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 4,4'-azobis(4-cyanovaleric acid), and 1,1'-azobis(1-cyclohexanecarbonitrile).
[0053] The photoradical polymerization initiator is a polymerization initiator that generates radicals by irradiation with light having a wavelength in the range of 150 to 750 nm, preferably light having a wavelength in the range of 254 to 405 nm, and more preferably light having a wavelength of 365 nm (e.g., ultraviolet light). The photopolymerization initiator is preferably a photoradical polymerization initiator from the viewpoint of easier curing at low temperature in a short time. Examples of the photoradical polymerization initiator include photopolymerization initiators having structures such as an oxime ester structure, a bisimidazole structure, an acridine structure, an α-aminoalkylphenone structure, an aminobenzophenone structure, an N-phenylglycine structure, an acylphosphine oxide structure, a benzyl dimethyl ketal structure, and an α-hydroxyalkylphenone structure.
[0054] Specific examples of compounds having an oxime ester structure include 1-phenyl-1,2-butanedione-2-(o-methoxycarbonyl)oxime, 1-phenyl-1,2-propanedione-2-(o-methoxycarbonyl)oxime, 1-phenyl-1,2-propanedione-2-(o-ethoxycarbonyl)oxime, 1-phenyl-1,2-propanedione-2-o-benzoyloxime, 1,3-diphenylpropanetrione-2-(o-ethoxycarbonyl)oxime, 1-phenyl-3-ethoxypropanetrione-2-(o-benzoyl)oxime, 1,2-octanedione, 1-[4-(phenylthio)phenyl-, 2-(o-benzoyloxime)], ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(o-acetyloxime), and the like.
[0055] Examples of compounds having a bisimidazole structure include 2,4,5-triarylimidazole dimers such as 2-(o-chlorophenyl)-4,5-diphenylimidazole dimer, 2-(o-chlorophenyl)-4,5-di(m-methoxyphenyl)imidazole dimer, 2-(o-fluorophenyl)-4,5-phenylimidazole dimer, 2-(o-methoxyphenyl)-4,5-diphenylimidazole dimer, 2-(p-methoxyphenyl)-4,5-diphenylimidazole dimer, 2,4-di(p-methoxyphenyl)-5-phenylimidazole dimer, and 2-(2,4-dimethoxyphenyl)-4,5-diphenylimidazole dimer.
[0056] Examples of compounds having an acridine structure include 9-phenylacridine and 1,7-bis(9,9'-acridinyl)heptane.
[0057] The content of the radical polymerization initiator may be 0.1% by mass or more, 0.5% by mass or more, or 1% by mass or more based on the total mass of the adhesive composition, from the viewpoint of further improving the effect of reducing the connection resistance and achieving better connection reliability. The content of the radical polymerization initiator may be 30% by mass or less, 20% by mass or less, or 10% by mass or less based on the total mass of the adhesive composition, from the viewpoint of pot life. From these viewpoints, the content of the radical polymerization initiator may be 0.1 to 30% by mass, 0.5 to 20% by mass, or 1 to 10% by mass based on the total mass of the adhesive composition.
[0058] <Epoxy group-containing acrylic resin> The epoxy group-containing acrylic resin is an acrylic resin having at least one epoxy group in the molecule. Here, the acrylic resin means a polymer containing a monomer unit derived from a (meth)acrylate compound. The epoxy group-containing acrylic resin may be a polymer containing only a monomer unit derived from a (meth)acrylate compound, or may be a polymer containing a monomer unit derived from a (meth)acrylate compound and a monomer unit derived from a polymerizable compound other than a (meth)acrylate compound.
[0059] Examples of the (meth)acrylate compound contained as a monomer unit in the epoxy group-containing acrylic resin include the (meth)acrylate compounds exemplified above as the radically polymerizable compound.
[0060] Polymerizable compounds other than (meth)acrylate compounds that can be contained as monomer units in the epoxy group-containing acrylic resin include compounds other than (meth)acrylate compounds exemplified above as the radically polymerizable compounds (maleimide compounds, vinyl ether compounds, allyl compounds, styrene, styrene derivatives, acrylamide derivatives, nadimide derivatives, natural rubber, isoprene rubber, butyl rubber, nitrile rubber, butadiene rubber, styrene-butadiene rubber, acrylonitrile-butadiene rubber, carboxylated nitrile rubber, etc.). Among these, styrene and styrene derivatives are preferably used.
[0061] The epoxy group-containing acrylic resin may be solid. The shape of the epoxy group-containing acrylic resin is not particularly limited, and may be, for example, powder or flake.
[0062] The weight average molecular weight of the epoxy group-containing acrylic resin is 5000 or more, and may be 7500 or more, 10000 or more, 15000 or more, or 20000 or more. When the weight average molecular weight of the epoxy group-containing acrylic resin is 5000 or more, not only excellent half-cutting properties are obtained, but also film formability is improved and good toughness tends to be obtained. The weight molecular weight of the epoxy group-containing acrylic resin may be 30000 or less, 20000 or less, 15000 or less, or 10000 or less, from the viewpoint of obtaining good fluidity during mounting and obtaining better connection resistance. In particular, when the weight molecular weight of the epoxy group-containing acrylic resin is 15000 or less, better adhesive strength is likely to be obtained. From these viewpoints, the weight average molecular weight of the epoxy group-containing acrylic resin may be 5,000 to 30,000, or may be 7,500 to 20,000, 7,500 to 15,000, 7,500 to 10,000, 10,000 to 30,000, 15,000 to 30,000, or 20,000 to 30,000.
[0063] The epoxy equivalent (unit: g / eq) of the epoxy group-containing acrylic resin may be 100 or more, 200 or more, or 300 or more from the viewpoint of excellent storage stability. The epoxy equivalent (unit: g / eq) of the epoxy group-containing acrylic resin is preferably 1000 or less from the viewpoint of suppressing the occurrence of warping of the cured product due to an increase in the curing shrinkage rate, and may be 500 or less, 350 or less, or 200 or less. In particular, when the epoxy equivalent (unit: g / eq) of the epoxy group-containing acrylic resin is 200 or less, a better adhesive strength is easily obtained. From these viewpoints, the epoxy equivalent (unit: g / eq) of the epoxy group-containing acrylic resin may be 100 to 1000, 200 to 500, 300 to 500, or 100 to 200. Here, the epoxy equivalent is the number of grams (g / eq) of a resin containing 1 gram equivalent of epoxy groups, and is measured according to the method specified in JIS K-7236.
[0064] The glass transition temperature (Tg) of the epoxy group-containing acrylic resin may be 25°C or higher, 35°C or higher, or 45°C or higher, from the viewpoint of improving the reliability resistance and the stability against external stress. The glass transition temperature (Tg) of the epoxy group-containing acrylic resin may be 100°C or lower, 80°C or lower, 60°C or lower, or 50°C or lower, from the viewpoint of preventing peeling after curing. In particular, when the glass transition temperature (Tg) of the epoxy group-containing acrylic resin is 60°C or lower, a better adhesive strength is easily obtained. From these viewpoints, the glass transition temperature (Tg) of the epoxy group-containing acrylic resin may be 25 to 100°C, 35 to 80°C, 45 to 60°C, 25 to 60°C, or 25 to 50°C. Here, the glass transition temperature is a value measured by differential scanning calorimetry.
[0065] The content of the epoxy group-containing acrylic resin may be 1% by mass or more, 5% by mass or more, or 10% by mass or more based on the total solid content contained in the adhesive composition from the viewpoint of further improving the half-cutting property. The content of the epoxy group-containing acrylic resin may be 15% by mass or less, 10% by mass or less, or 5% by mass or less based on the total solid content contained in the adhesive composition from the viewpoint of easily obtaining a homogeneous composition by mixing the epoxy group-containing acrylic resin well with other components (radical polymerizable compound, etc.) in the composition. From these viewpoints, the content of the epoxy group-containing acrylic resin may be 1 to 15% by mass, 5 to 15% by mass, or 10 to 15% by mass based on the total solid content contained in the adhesive composition. Note that the total solid content means the amount obtained by excluding the amount of the solvent from the total amount of the adhesive composition when the adhesive composition contains a solvent, and means the total amount of the adhesive composition when the adhesive composition does not contain a solvent. However, the solid content does not include conductive particles.
[0066] <Conductive particles> The conductive particles are not particularly limited as long as they are conductive particles, and may be metal particles made of metals such as Au, Ag, Ni, Cu, solder, etc., or conductive carbon particles made of conductive carbon. The conductive particles may be coated conductive particles having a core containing non-conductive glass, ceramic, plastic (polystyrene, etc.), etc., and a coating layer containing the above metal or conductive carbon and coating the core. Among these, metal particles formed of a heat-fusible metal, or coated conductive particles having a core containing plastic and a coating layer containing a metal or conductive carbon and coating the core are preferably used. In this case, since the cured product of the adhesive composition can be easily deformed by heating or pressure, when the electrodes are electrically connected to each other, the contact area between the electrodes and the conductive particles can be increased, and the conductivity between the electrodes can be further improved.
[0067] The conductive particles may be insulating coated conductive particles comprising the above-mentioned metal particles, conductive carbon particles or coated conductive particles, and an insulating layer containing an insulating material such as resin and coating the surface of the particles. When the conductive particles are insulating coated conductive particles, even if the content of the conductive particles is high, the surface of the particles is coated with resin, so that the occurrence of short circuits due to contact between the conductive particles can be suppressed, and the insulation between adjacent electrode circuits can be improved. The conductive particles are used as one of the above-mentioned various conductive particles alone or in combination of two or more.
[0068] The maximum particle size of the conductive particles must be smaller than the minimum interval between the electrodes (the shortest distance between adjacent electrodes). From the viewpoint of excellent dispersibility and conductivity, the maximum particle size of the conductive particles may be 1.0 μm or more, 2.0 μm or more, or 2.5 μm or more. From the viewpoint of excellent dispersibility and conductivity, the maximum particle size of the conductive particles may be 50 μm or less, 30 μm or less, or 20 μm or less. From these viewpoints, the maximum particle size of the conductive particles may be 1.0 to 50 μm, 2.0 to 30 μm, or 2.5 to 20 μm. In this specification, the particle size of 300 arbitrary conductive particles (pcs) is measured by observation using a scanning electron microscope (SEM), and the largest value obtained is defined as the maximum particle size of the conductive particles. In addition, when the conductive particles are not spherical, such as having protrusions, the particle size of the conductive particles is defined as the diameter of a circle circumscribing the conductive particles in an SEM image.
[0069] The average particle size of the conductive particles may be 1.0 μm or more, 2.0 μm or more, or 2.5 μm or more, from the viewpoint of excellent dispersibility and conductivity. The average particle size of the conductive particles may be 50 μm or less, 30 μm or less, or 20 μm or less, from the viewpoint of excellent dispersibility and conductivity. From these viewpoints, the average particle size of the conductive particles may be 1.0 to 50 μm, 2.0 to 30 μm, or 2.5 to 20 μm. In this specification, the particle size of any 300 conductive particles (pcs) is measured by observation using a scanning electron microscope (SEM), and the average value of the particle sizes obtained is defined as the average particle size.
[0070] When the adhesive composition is a composition used to form an insulating adhesive layer of an adhesive film, the content of conductive particles is preferably less than 0.1 vol. %, and more preferably 0 vol. %, based on the total volume of the adhesive composition.
[0071] When the adhesive composition is a composition used to form a conductive adhesive layer, the content of the conductive particles may be 0.1 volume % or more, 1 volume % or more, or 5 volume % or more, and 50 volume % or less, 30 volume % or less, or 20 volume % or less, or 0.1 to 50 volume %, 1 to 30 volume %, or 5 to 20 volume %, based on the total volume of the adhesive composition. When the content of the conductive particles is equal to or more than the above lower limit, the conductivity can be further improved. When the content of the conductive particles is equal to or less than the above upper limit, short circuits are easily suppressed.
[0072] <Thermoplastic resin> Examples of the thermoplastic resin include phenoxy resin, polyester resin, polyurethane resin, polyester urethane resin, butyral resin, acrylic resin (acrylic rubber, etc., excluding resins corresponding to the epoxy group-containing acrylic resin), polyimide resin, polyamide resin, etc. When the adhesive composition contains a thermoplastic resin, the adhesive composition can be easily molded into a film. When the adhesive composition contains a thermoplastic resin, the stress of the adhesive film generated during curing can be alleviated. When the thermoplastic resin has a functional group such as a hydroxyl group, the adhesive property of the adhesive film is likely to be improved. From this viewpoint, it is preferable to use at least one thermoplastic resin selected from the group consisting of phenoxy resin, polyester resin, polyurethane resin, polyester urethane resin, butyral resin, acrylic resin, and polyimide resin, and it is more preferable to use a phenoxy resin.
[0073] The content of the thermoplastic resin may be 5% by mass or more, 80% by mass or less, or may be 5 to 80% by mass, based on the total mass of the adhesive composition.
[0074] <Other ingredients> The adhesive composition may further contain components other than those described above (other components), such as coupling agents, fillers, softeners, accelerators, anti-deterioration agents, colorants, flame retardants, and thixotropic agents.
[0075] (Coupling Agent) As the coupling agent, a silane coupling agent having an organic functional group such as a (meth)acryloyl group, a mercapto group, an amino group, an imidazole group, or an epoxy group, a silane compound such as a tetraalkoxysilane, a tetraalkoxytitanate derivative, or a polydialkyltitanate derivative can be used. When the adhesive composition contains a coupling agent, the adhesiveness can be further improved. The content of the coupling agent may be, for example, 0.1 mass% or more, 20 mass% or less, or 0.1 to 20 mass% based on the total mass of the adhesive composition. In this specification, a silane coupling agent having a radical polymerizable group such as a (meth)acryloyl group is not included in the radical polymerizable compound.
[0076] (filling material) The filler may, for example, be a non-conductive filler (eg, non-conductive particles). When the adhesive composition contains a filler, it is expected that the connection reliability will be further improved. The filler may be either an inorganic filler or an organic filler. Examples of the inorganic filler include metal oxide fine particles such as silica fine particles, alumina fine particles, silica-alumina fine particles, titania fine particles, and zirconia fine particles; and inorganic fine particles such as nitride fine particles. Examples of the organic filler include organic fine particles such as silicone fine particles, methacrylate-butadiene-styrene fine particles, acrylic-silicone fine particles, polyamide fine particles, and polyimide fine particles. These fine particles may have a uniform structure or a core-shell structure. The content of the filler may be, for example, 1% by volume or more, 30% by volume or less, or 1 to 30% by volume based on the total volume of the adhesive composition.
[0077] <Adhesive film> Another embodiment of the present disclosure is an adhesive film (film-like adhesive) that includes a first adhesive layer made of the adhesive composition of the above embodiment.
[0078] The adhesive film of the present embodiment has excellent half-cutting properties because it contains a first adhesive layer made of the adhesive composition of the above embodiment. The adhesive film of the present embodiment is also suitable for circuit connection, and the adhesive film can easily provide a circuit connection structure having sufficiently high adhesive strength and sufficiently low connection resistance between opposing electrodes.
[0079] The adhesive film may be a single-layer adhesive film consisting of only the first adhesive layer, or may be a multi-layer adhesive film further including a second adhesive layer laminated on the first adhesive layer. The adhesive film may be composed of three or more layers including a layer other than the first adhesive layer and the second adhesive layer (e.g., a third adhesive layer).
[0080] The adhesive film may be an adhesive film containing conductive particles. When the adhesive film is a multi-layer adhesive film, any layer may contain conductive particles, but from the viewpoint of excellent half-cutting properties, it is preferable that the first adhesive layer does not substantially contain conductive particles. Here, "not substantially containing conductive particles" means that the content of conductive particles based on the total volume of the adhesive layer is less than 0.1 volume %.
[0081] The adhesive film containing conductive particles may be, for example, an adhesive film consisting of a first adhesive layer containing conductive particles, or may be an adhesive film including a first adhesive layer and a second adhesive layer, at least one of the first adhesive layer and the second adhesive layer containing conductive particles. The adhesive film containing conductive particles may have anisotropic conductivity or may not have anisotropic conductivity.
[0082] The adhesive film may be insulating or conductive. The adhesive film may be an adhesive film consisting of an insulating adhesive layer or a conductive adhesive layer, or may be an adhesive film including an insulating adhesive layer and a conductive adhesive layer. When the adhesive film includes an insulating adhesive layer and a conductive adhesive layer, one of the first adhesive layer and the second adhesive layer may be an insulating adhesive layer, and the other may be a conductive adhesive layer. The conductive adhesive layer and the insulating adhesive layer may be distinguished by the content of the conductive particles described above. That is, the insulating adhesive layer may be, for example, an adhesive layer in which the content of the conductive particles is less than 0.1 vol.% based on the total volume of the adhesive layer. Also, the conductive adhesive layer may be, for example, an adhesive layer in which the content of the conductive particles is 0.1 vol.% or more based on the total volume of the adhesive layer.
[0083] From the viewpoint of suppressing the flow of conductive particles occurring during the manufacture of the circuit connection structure, the adhesive film may include a layer made of a cured product of a photo- and heat-curable composition containing conductive particles (for example, a composition containing a polymerizable compound, a photopolymerization initiator, a heat polymerization initiator, and conductive particles) as the second adhesive layer. With such an adhesive film containing a second adhesive layer, it is possible to suppress the occurrence of short circuits caused by the aggregation of conductive particles between electrodes, as well as the deterioration of insulation properties and the occurrence of variations in connection resistance values caused by the distribution of sparseness and density of conductive particles accompanying the flow of conductive particles. As the polymerizable compound, photopolymerization initiator, and heat polymerization initiator, for example, the above-mentioned radical polymerizable, photoradical polymerization initiator, and heat radical polymerization initiator can be used.
[0084] The adhesive film of this embodiment will be described in detail below, taking as an example a two-layer adhesive film for circuit connection.
[0085] Fig. 1 is a schematic cross-sectional view showing an adhesive film for circuit connection of one embodiment. The adhesive film for circuit connection 1 (hereinafter also simply referred to as "adhesive film 1") shown in Fig. 1 comprises a first adhesive layer 2 and a second adhesive layer 3 laminated on the first adhesive layer 2. At least one of the first adhesive layer 2 and the second adhesive layer 3 is made of the adhesive composition of the above embodiment. Hereinafter, the adhesive composition constituting the first adhesive layer 2 may be referred to as the first adhesive composition, and the adhesive composition constituting the second adhesive layer may be referred to as the second adhesive composition, depending on the circumstances.
[0086] (First adhesive layer) The first adhesive layer 2 is an insulating adhesive layer. The content of the conductive particles in the first adhesive layer 2 is, for example, less than 0.1% by volume based on the total volume of the first adhesive layer 2. The first adhesive layer 2 does not need to contain conductive particles.
[0087] The thickness d1 of the first adhesive layer 2 may be appropriately set according to the height of the electrodes of the circuit members to be bonded. The thickness d1 of the first adhesive layer 2 may be 5 μm or more, 200 μm or less, or 5 to 200 μm, from the viewpoint of being able to sufficiently fill the space between the electrodes to seal the electrodes and obtain better connection reliability. As described later, when a part of the conductive particles 4 is exposed from the surface of the second adhesive layer 3 (for example, protruding toward the first adhesive layer 2 side), the distance (distance indicated by d1 in FIG. 1) from the surface 2a of the first adhesive layer 2 opposite to the second adhesive layer 3 side to the boundary S between the first adhesive layer 2 and the second adhesive layer 3 located in the space between the adjacent conductive particles 4, 4 is the thickness of the first adhesive layer 2.
[0088] The thickness of the adhesive layer can be measured by the following method. First, the adhesive film 1 is sandwiched between two pieces of glass (thickness: about 1 mm). Next, a resin composition consisting of 100 g of bisphenol A type epoxy resin (product name: JER811, manufactured by Mitsubishi Chemical Corporation) and 10 g of a hardener (product name: Epomount hardener, manufactured by Refine Tech Co., Ltd.) is cast. Then, the cross section is polished using a polishing machine, and the thickness of each adhesive layer is measured using a scanning electron microscope (SEM, product name: SE-8020, manufactured by Hitachi High-Tech Science Corporation).
[0089] (Second adhesive layer) The second adhesive layer 3 is a conductive adhesive layer. The second adhesive layer 3 contains conductive particles 4 and an adhesive component 5. The content of the conductive particles 4 in the second adhesive layer 3 may be 0.1 volume % or more, 1 volume % or more, or 5 volume % or more based on the total volume of the second adhesive layer 3 from the viewpoint of further improving the conductivity. The content of the conductive particles 4 in the second adhesive layer 3 may be 50 volume % or less, 30 volume % or less, or 20 volume % or less based on the total volume of the second adhesive layer 3 from the viewpoint of easily suppressing short circuits. From these viewpoints, the content of the conductive particles 4 in the second adhesive layer 3 may be 0.1 to 50 volume %, 1 to 30 volume %, or 5 to 20 volume % based on the total volume of the second adhesive layer 3.
[0090] The thickness d2 of the second adhesive layer 3 may be 0.1 times or more, 0.2 times or more, or 0.3 times or more of the average particle size of the conductive particles 4 from the viewpoint of making the conductive particles 4 more easily trapped between the opposing electrodes and further reducing the connection resistance. The thickness d2 of the second adhesive layer 3 may be 0.8 times or less, or 0.7 times or less of the average particle size of the conductive particles 4 from the viewpoint of making the conductive particles 4 more easily crushed when sandwiched between the opposing electrodes during thermocompression bonding and further reducing the connection resistance. From these viewpoints, the thickness d2 of the second adhesive layer 3 may be 0.1 to 0.8 times, 0.2 to 0.8 times, or 0.3 to 0.7 times the average particle size of the conductive particles 4. The thickness d2 of the second adhesive layer 3 refers to the thickness of the second adhesive layer located in the space between the adjacent conductive particles 4, 4.
[0091] When the thickness d2 of the second adhesive layer 3 and the average particle size of the conductive particles 4 satisfy the above-mentioned relationship, for example, as shown in FIG. 1, a part of the conductive particles 4 in the second adhesive layer 3 may protrude from the second adhesive layer 3 to the first adhesive layer 2 side. In this case, the boundary S between the second adhesive layer 3 and the first adhesive layer 2 is located in the space between the adjacent conductive particles 4, 4. By having the boundary S on the conductive particles 4 along the surface of the conductive particles 4, the conductive particles 4 in the second adhesive layer 3 may satisfy the above-mentioned relationship without protruding from the second adhesive layer 3 to the first adhesive layer 2 side. The conductive particles 4 are not exposed on the surface 3a of the second adhesive layer 3 opposite to the first adhesive layer 2 side, and the opposite surface 3a may be a flat surface.
[0092] The relationship between the thickness d2 of the second adhesive layer 3 and the maximum particle size of the conductive particles 4 may be the same as above. For example, the thickness d2 of the second adhesive layer 3 may be 0.1 to 0.8 times, 0.2 to 0.8 times, or 0.3 to 0.7 times the maximum particle size of the conductive particles 4.
[0093] The thickness d2 of the second adhesive layer 3 may be, for example, 0.5 μm or more, 20 μm or less, or 0.5 to 20 μm. When a part of the conductive particles 4 is exposed from the surface of the second adhesive layer 3 (for example, protruding toward the first adhesive layer 2 side), the shortest distance (distance shown as d2 in FIG. 1) from the surface 3a of the second adhesive layer 3 opposite to the first adhesive layer 2 side to the boundary S between the second adhesive layer 3 and the first adhesive layer 2 located in the space between the adjacent conductive particles 4, 4 is the thickness of the second adhesive layer 3, and the exposed part of the conductive particles 4 is not included in the thickness of the second adhesive layer 3. The length of the exposed part of the conductive particles 4 may be, for example, 0.1 μm or more, 20 μm or less, or 0.1 to 20 μm.
[0094] The ratio of the thickness d2 of the second adhesive layer 3 to the thickness d1 of the first adhesive layer 2 (thickness d2 of the second adhesive layer 3 / thickness d1 of the first adhesive layer 2) may be 1 or more and 100 or less, from the viewpoint of being able to sufficiently fill the space between the electrodes to seal the electrodes and obtain better reliability.
[0095] The thickness of the adhesive film 1 (the total thickness of all layers constituting the adhesive film 1) may be, for example, 5 μm or more and 200 μm or less, or may be 5 to 200 μm.
[0096] In the adhesive film 1, conductive particles 4 are dispersed in the second adhesive layer 3. Therefore, the adhesive film 1 is an anisotropically conductive adhesive film having anisotropic conductivity. The adhesive film 1 is interposed between a first circuit member having a first electrode and a second circuit member having a second electrode, and is used for thermocompression bonding the first circuit member and the second circuit member to electrically connect the first electrode and the second electrode to each other.
[0097] Either the first adhesive layer 2 or the second adhesive layer 3 may be made of an adhesive composition that does not contain an epoxy group-containing acrylic resin. The adhesive composition may contain a component that can be contained in the adhesive composition of the above embodiment (a component other than the epoxy group-containing acrylic resin), and may be, for example, a composition that contains a radical polymerizable compound and a radical polymerization initiator.
[0098] The second adhesive layer 3 may be a layer made of a cured product of the photo- and thermosetting composition containing the above-mentioned conductive particles. In this case, the first adhesive layer 2 is made of the adhesive composition of the above-mentioned embodiment.
[0099] The adhesive film 1 can be manufactured, for example, by a method including a step of preparing a first adhesive layer 2 (first preparation step), a step of preparing a second adhesive layer 3 (second preparation step), and a step of laminating the first adhesive layer 2 and the second adhesive layer 3 (lamination step).
[0100] (First preparation step) In the first preparation step, for example, a first adhesive layer 2 is formed on a substrate. Specifically, for example, each component contained in the first adhesive composition is added to a solvent (organic solvent) and dissolved or dispersed by stirring, mixing, kneading, etc. to prepare a varnish composition (varnish-like first adhesive composition). Thereafter, the varnish composition is applied to a substrate that has been subjected to a release treatment using a knife coater, roll coater, applicator, comma coater, die coater, etc., and the solvent is volatilized by heating to form a first adhesive layer 2 made of the first adhesive composition.
[0101] The solvent used in preparing the varnish composition is preferably one that has the property of dissolving or dispersing each component uniformly, and examples thereof include toluene, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, propyl acetate, butyl acetate, etc. These solvents can be used alone or in combination of two or more. The stirring and mixing and kneading in preparing the varnish composition can be performed using, for example, a stirrer, a grinding machine, a three-roll mill, a ball mill, a bead mill, or a homodisper.
[0102] The substrate is not particularly limited as long as it has heat resistance sufficient to withstand the heating conditions for volatilizing the solvent. For example, substrates (e.g., films) made of oriented polypropylene (OPP), polyethylene terephthalate (PET), polyethylene naphthalate, polyethylene isophthalate, polybutylene terephthalate, polyolefin, polyacetate, polycarbonate, polyphenylene sulfide, polyamide, polyimide, cellulose, ethylene-vinyl acetate copolymer, polyvinyl chloride, polyvinylidene chloride, synthetic rubber, liquid crystal polymer, etc. can be used.
[0103] The heating conditions (drying conditions) for volatilizing the solvent from the varnish composition applied to the substrate are preferably conditions that allow the solvent to volatilize sufficiently, for example, at 40° C. or higher and 120° C. or lower for 0.1 minutes or longer and 10 minutes or shorter.
[0104] A portion of the solvent may remain unremoved in the first adhesive layer 2. The content of the solvent in the first adhesive layer 2 may be, for example, 10 mass % or less based on the total mass of the first adhesive layer 2.
[0105] (Second preparation step) In the second preparation step, for example, a second adhesive layer 3 is formed on a substrate. Specifically, for example, a layer made of a second adhesive composition is formed on a substrate in the same manner as in the first preparation step. The types of solvents that can be used, the types of substrates, and drying conditions are the same as those in the case of the first adhesive layer. Next, when the second adhesive composition is a photo- and thermosetting composition, the layer made of the second adhesive composition is irradiated with light to cure (photo-cure) the second adhesive composition, thereby forming a second adhesive layer 3 on the substrate.
[0106] A portion of the solvent may remain unremoved in the second adhesive layer 3. The content of the solvent in the second adhesive layer 3 may be, for example, 10 mass % or less based on the total mass of the second adhesive layer 3.
[0107] For the light irradiation, it is preferable to use light having a wavelength in the range of 150 to 750 nm (for example, ultraviolet light). For example, the light irradiation can be performed using a low pressure mercury lamp, a medium pressure mercury lamp, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a xenon lamp, a metal halide lamp, an LED light source, or the like. The amount of light irradiation is not particularly limited, and for example, the integrated light amount of light having a wavelength of 365 nm is 100 mJ / cm. 2 or more, and 2 or more, 300 mJ / cm 2 The amount of light irradiation may be, for example, 10,000 mJ / cm2 in terms of the integrated light amount of light with a wavelength of 365 nm. 2 may be less than 5000 mJ / cm 2 or less than 3000 mJ / cm 2 It may be the following:
[0108] (Lamination process) In the lamination step, the first adhesive layer 2 and the second adhesive layer 3 are laminated by bonding the first adhesive layer 2 and the second adhesive layer 3. Examples of a method for bonding the first adhesive layer 2 and the second adhesive layer 3 include a method such as hot pressing, roll lamination, and vacuum lamination. The lamination may be performed, for example, under a temperature condition of 0 to 80°C.
[0109] Although the method for producing the adhesive film for circuit connection 1 has been described above, the method for producing the adhesive film for circuit connection 1 is not limited to the above embodiment.
[0110] For example, the second adhesive layer 3 may be prepared in the second preparation step, and then the first adhesive layer 2 may be formed directly on the second adhesive layer 3 in the same manner as in the first preparation step, to obtain the adhesive film 1 for circuit connection. The order in which the first preparation step and the second preparation step are performed is not limited. The first preparation step may be performed first, or the second preparation step may be performed first. For example, when the second adhesive composition is a photo- and thermosetting composition, the adhesive film 1 for circuit connection may be obtained by preparing a laminate including a layer made of the second adhesive composition and a layer made of the first adhesive composition, and then irradiating the laminate with light to cure the second adhesive composition.
[0111] <Laminate> Another embodiment of this embodiment is a laminate including a substrate and the adhesive film of the above embodiment provided on the substrate. As the substrate, those exemplified as substrates used in the manufacture of the adhesive film 1 can be used.
[0112] <Method of Manufacturing Circuit Connection Structure> Another embodiment of this embodiment is a method for producing a circuit connection structure, comprising: a half-cutting step of cutting the adhesive film of the laminate of the above embodiment along an outline line forming the outline of the adhesive film piece; a step of peeling the adhesive film piece formed by the half-cutting step from the substrate; and a step of interposing the adhesive film piece between a first circuit member having a first electrode and a second circuit member having a second electrode, and thermocompressing the first circuit member and the second circuit member to electrically connect the first electrode and the second electrode to each other.
[0113] The method for producing the circuit connection structure of this embodiment will be described below by taking as an example a method using a laminate including the above-mentioned adhesive film 1.
[0114] 2 and 3 are schematic cross-sectional views showing a method for manufacturing the circuit connection structure 10 of one embodiment.
[0115] In the method for manufacturing the circuit connection structure 10, first, a laminate 7 including a substrate 6 and an adhesive film 1 provided on the substrate 6 is prepared, and a half-cut process is performed on the laminate 7 (see FIGS. 2(a) and (b)). In the half-cut process, the adhesive film 1 of the laminate 7 is cut along an outline 8a that defines the outline of the adhesive film piece 8. At this time, a cut is made from the adhesive film 1 side to the surface of the substrate 6 so as not to cut the substrate 6. The half-cut process can be performed using a known half-cut blade.
[0116] Next, the adhesive film piece 8 formed by the half-cutting process is peeled off from the base material 6 (see FIG. 2(c)). At this time, since the adhesive film 1 is used in this embodiment, the adhesive is unlikely to reattach at the cut portion, and the adhesive film piece 8 can be easily peeled off from the base material 6.
[0117] Next, a first circuit board 11 and a first circuit member 13 having a first electrode 12 formed on the main surface 11a of the first circuit board 11, and a second circuit board 14 and a second circuit member 16 having a second electrode 15 formed on the main surface 14a of the second circuit board 14 are prepared, and the first circuit member 13 and the second circuit member 16 are arranged so that the first electrode 12 and the second electrode 15 face each other, and a piece of adhesive film 8 is arranged between the first circuit member 13 and the second circuit member 16 (see (a) of Figure 3).
[0118] The first circuit member 13 and the second circuit member 16 may be the same or different from each other. The first circuit member 13 and the second circuit member 16 may be a glass substrate or a plastic substrate on which electrodes are formed, a printed wiring board, a ceramic wiring board, a flexible wiring board, a semiconductor silicon IC chip, or the like. The first circuit board 11 and the second circuit board 14 may be formed of an inorganic material such as a semiconductor, glass, or ceramic, an organic material such as polyimide or polycarbonate, or a composite material such as glass / epoxy, or the like. The first electrode 12 and the second electrode 15 may be formed of gold, silver, tin, ruthenium, rhodium, palladium, osmium, iridium, platinum, copper, aluminum, molybdenum, titanium, indium tin oxide (ITO), indium zinc oxide (IZO), indium gallium zinc oxide (IGZO), or the like. The first electrode 12 and the second electrode 15 may be circuit electrodes or bump electrodes. At least one of the first electrode 12 and the second electrode 15 may be a bump electrode. In FIG. 3, the second electrode 15 is a bump electrode.
[0119] There is no particular limitation on the order in which the first circuit member 13, the second circuit member 16, and the adhesive film piece 8 are arranged. For example, the adhesive film piece 8 may be laminated onto the first circuit member 13 so that the second adhesive layer 3 side faces the mounting surface 11a of the first circuit member 13, and then the second circuit member 16 may be arranged on the first circuit member 13 on which the adhesive film piece 8 has been laminated so that the first electrode 12 on the first circuit board 11 and the second electrode 15 on the second circuit board 14 face each other.
[0120] Next, the first circuit member 13, the adhesive film piece 8, and the second circuit member 16 are heated while the first circuit member 13 and the second circuit member 16 are pressed in the thickness direction to thermocompress the first circuit member 13 and the second circuit member 16 together (see FIG. 3(b)). At this time, as shown by the arrow in FIG. 3(b), the first adhesive layer 2 is made of a flowable uncured thermosetting composition (first adhesive composition), so that it flows to fill the gap between the second electrodes 15, 15 and is cured by the above heating. As a result, the first electrode 12 and the second electrode 15 are electrically connected to each other via the conductive particles 4, and the first circuit member 13 and the second circuit member 16 are bonded to each other by the cured product 17 of the adhesive film piece 8, thereby obtaining the circuit connection structure 10 shown in FIG. 3(c). The cured product 17 of the adhesive film piece 8 is located on the second circuit member 16 side in the direction in which the first circuit member 13 and the second circuit member 16 face each other (hereinafter referred to as the "facing direction") and is composed of a first region 18 consisting of a cured product of the above-mentioned first adhesive composition, a second region 19 located on the first circuit member 13 side in the facing direction and consisting of a cured product of components of the above-mentioned second adhesive composition other than the conductive particles 4, and conductive particles 4 interposed at least between the first electrode 12 and the second electrode 15 to electrically connect the first electrode 12 and the second electrode 15 to each other.
[0121] In the manufacturing method of the circuit connection structure 10, since the second adhesive layer 3 is a pre-cured layer, the conductive particles 4 hardly flow during the thermocompression bonding and are efficiently captured between the opposing electrodes, thereby reducing the connection resistance between the opposing electrodes 12 and 15. As a result, a circuit connection structure with excellent connection reliability can be obtained. EXAMPLES
[0122] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the following examples.
[0123] <Synthesis of polyurethane acrylate (UA1)> Into a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser having a calcium chloride drying tube, and a nitrogen gas inlet tube, 2500 parts by mass (2.50 mol) of poly(1,6-hexanediol carbonate) (trade name: Duranol T5652, manufactured by Asahi Kasei Chemicals Corporation, number average molecular weight 1000) and 666 parts by mass (3.00 mol) of isophorone diisocyanate (manufactured by Sigma-Aldrich Co.) were uniformly dropped over 3 hours. Next, after sufficient nitrogen gas was introduced into the reaction vessel, the inside of the reaction vessel was heated to 70 to 75°C to cause a reaction. Next, 0.53 parts by mass (4.3 mmol) of hydroquinone monomethyl ether (Sigma-Aldrich) and 5.53 parts by mass (8.8 mmol) of dibutyltin dilaurate (Sigma-Aldrich) were added to the reaction vessel, and then 238 parts by mass (2.05 mol) of 2-hydroxyethyl acrylate (Sigma-Aldrich) were added and reacted at 70°C for 6 hours under air atmosphere. This resulted in polyurethane acrylate (UA1). The weight-average molecular weight of polyurethane acrylate (UA1) was 15,000. The weight-average molecular weight was measured by gel permeation chromatography (GPC) using a calibration curve based on standard polystyrene under the following conditions. (Measurement conditions) Equipment: Tosoh Corporation GPC-8020 Detector: Tosoh RI-8020 Column: Gelpack GLA160S+GLA150S manufactured by Hitachi Chemical Co., Ltd. Sample concentration: 120mg / 3mL Solvent: Tetrahydrofuran Injection volume: 60μL Pressure: 2.94×10 6 Pa(30kgf / cm 2 ) Flow rate: 1.00mL / min
[0124] <Preparation of conductive particles> A layer of nickel was formed on the surface of the polystyrene particles to a thickness of 0.2 μm, thus obtaining conductive particles with an average particle size of 4 μm, a maximum particle size of 4.5 μm, and a specific gravity of 2.5.
[0125] <Examples 1 to 4 and Comparative Example 1> (Preparation of varnish-like adhesive composition (varnish composition)) The components shown below were mixed together with a solvent (methyl ethyl ketone) to prepare varnish compositions 1 to 6. The amount of each component (parts by mass) is shown in Table 1. The amount of A1 is the solid content of the thermoplastic resin solution. The amount of the solvent was adjusted so that the solid content of the varnish composition was 50% by mass.
[0126] [Thermoplastic resin solution] A1: A solution with a solid content concentration of 40% by mass prepared by dissolving 40 g of bisphenol A type phenoxy resin (product name: PKHC, manufactured by Union Carbide) in 60 g of methyl ethyl ketone.
[0127] [Radical polymerizable compounds] B1: Polyurethane acrylate (UA1) synthesized as described above B2: Diacrylate having a tricyclodecane skeleton (product name: DCP-A, manufactured by Toagosei Co., Ltd.) B3: 2-Methacryloyloxyethyl acid phosphate (product name: Light Ester P-2M, manufactured by Kyoeisha Chemical Co., Ltd.) Manufactured by Gaku Co., Ltd.)
[0128] [Epoxy group-containing acrylic resin] C1: Acrylic resin having at least one epoxy group in the molecule (product name: Marproof G-01100, manufactured by NOF Corporation, weight average molecular weight: 10,000, epoxy equivalent: 170 g / eq, Tg: 47°C) ) C2: Acrylic resin having at least one epoxy group in the molecule (product name: Marproof G-0150M, manufactured by NOF Corporation, weight average molecular weight: 10,000, epoxy equivalent: 310 g / eq, Tg: 71°C) C3: Acrylic resin having at least one epoxy group in the molecule (product name: Marproof G-0250SP, manufactured by NOF Corporation, weight average molecular weight: 20,000, epoxy equivalent: 310 g / eq, Tg: 74°C)
[0129] [Conductive particles] D1: Conductive particles prepared as described above
[0130] (Thermal radical polymerization initiator) E1: Benzoyl peroxide (product name: Niper BMT-K40, manufactured by NOF Corporation)
[0131] [Table 1]
[0132] (Preparation of the first laminate) In Example 1, a first laminate was produced using the varnish composition 1. Specifically, the varnish composition 1 was first applied to a PET film having a thickness of 50 μm using a coating device. Then, hot air drying was performed at 70° C. for 3 minutes to form an insulating adhesive layer (insulating adhesive film) having a thickness of 8 μm on the PET film. Through the above operations, a first laminate (laminate 1) having an insulating adhesive layer (insulating adhesive film) on the PET film was obtained.
[0133] In Examples 2 to 4 and Comparative Example 1, first laminates (laminates 2 to 5) each having an insulating adhesive layer (insulating adhesive film) on a PET film were prepared in the same manner as described above, except that varnish compositions 2 to 5 were used instead of varnish composition 1.
[0134] (Preparation of the second laminate) A second laminate was produced using the varnish composition 6. Specifically, the varnish composition 6 was first applied onto a PET film having a thickness of 50 μm using a coating device. Next, hot air drying was performed at 70° C. for 3 minutes to form a second adhesive layer having a thickness (thickness after drying) of 4 μm on the PET film. Through the above operations, a second laminate (laminate 6) having a conductive adhesive layer (conductive adhesive film) on the PET film was obtained. The conductive particle density at this time was about 7000 pcs / mm 2The thickness of the region where the conductive particles are present, measured using a contact thickness meter, was 4 μm. If the thickness of the conductive adhesive layer is smaller than the thickness (diameter) of the conductive particles, the thickness of the layer measured using a contact thickness meter will reflect the thickness of the conductive particles, and the thickness of the region where the conductive particles are present will be measured. Therefore, the thickness of the conductive adhesive layer was measured by measuring the thickness of the conductive adhesive layer located in the space between adjacent conductive particles after producing an adhesive film for circuit connection, which will be described later.
[0135] (Preparation of a laminate with an adhesive film for circuit connection) The first laminate and the second laminate were placed so that their adhesive layers faced each other, and were laminated with a roll laminator while being heated together with the PET film substrate at 40° C. In this way, the laminates of Examples 1 to 4 and Comparative Example 1, each including a substrate and an adhesive film for circuit connection (two-layer adhesive film) provided on the substrate, were produced.
[0136] The thickness of the conductive adhesive layer of the prepared adhesive film for circuit connection was measured by the following method. First, the circuit connection adhesive film was sandwiched between two pieces of glass (thickness: about 1 mm) and a resin composition consisting of 100 g of bisphenol A type epoxy resin (product name: JER811, manufactured by Mitsubishi Chemical Corporation) and 10 g of a hardener (product name: Epomount hardener, manufactured by Refine Tech Co., Ltd.) was poured into the mold. Then, the cross section was polished using a polishing machine, and the thickness of the conductive adhesive layer located in the space between adjacent conductive particles was measured using a scanning electron microscope (SEM, product name: SE-8020, manufactured by Hitachi High-Tech Science Co., Ltd.). The thickness of the conductive adhesive layer was 2 μm.
[0137] (Half-cut performance evaluation) The half-cut property of the adhesive film for circuit connection obtained above was evaluated using a thermocompression bonding device LD-06 manufactured by Ohashi Manufacturing Co., Ltd. A specific evaluation method will be described with reference to Fig. 4. In Fig. 4, 21 is the laminate obtained above, 22 is the substrate, and 23 is the adhesive film for circuit connection (two-layer adhesive film).
[0138] First, the half-cut blade was collided with the laminate 21 obtained above, and only the adhesive film 23 was cut. At this time, the contact position of the half-cut blade on the surface of the substrate 22 was set as the cutting reference position, and the blade depth (cut depth from the cutting reference position) was set to 5 μm. Next, the substrate 22 side of the laminate 21 after half-cutting was fixed on a flat plate 25 using an adhesive tape 24, and one of the adhesive films (adhesive film piece 23a) divided based on the cut surface 26 was pinched and lifted up, and peeled off to the cut surface 26. At this time, the degree of lifting of the other adhesive film (adhesive film piece 23b) divided based on the cut surface was confirmed. The above operation was performed at five points, and a state in which there was no lifting at all was designated A, a state in which there was some lifting at least once was designated B, and a state in which there was significant lifting at least once or peeling off together with the adhesive film piece 23a was designated C.
[0139] (Evaluation of circuit connection structures) A 25 μm pitch COF (manufactured by FLEXSEED Co., Ltd.) and a glass substrate (manufactured by Geomatec Co., Ltd.) with a thin-film electrode (height: 1200 Å) made of amorphous indium tin oxide (ITO) on a glass substrate were connected over a width of 1 mm using a thermocompression bonding device (heating method: constant heat type, manufactured by Taiyo Kikai Seisakusho Co., Ltd.) under conditions of 170° C., 6 MPa, and 4 seconds to produce a circuit connection structure (connection structure). Note that, when connecting, the circuit connection adhesive film was placed on the glass substrate so that the adhesive layer side of the circuit connection adhesive film faced the glass substrate.
[0140] [Connection resistance measurement] The connection resistance between the opposing electrodes of the circuit connection structure obtained above was measured with a multimeter. The connection resistance was calculated as the average value of 16 resistance points between the opposing electrodes. The results are shown in Table 2.
[0141] [Adhesive strength measurement] The adhesive strength of the circuit connection structure obtained above was measured by a 90-degree peel method in accordance with JIS-Z0237. The adhesive strength was measured using a Tensilon UTM-4 (product name, manufactured by Toyo Baldwin Co., Ltd., peel strength 50 mm / min, 25°C). The results are shown in Table 2. [Table 2] [Explanation of symbols]
[0142] 1...adhesive film for circuit connection, 2...first adhesive layer, 3...second adhesive layer, 4...conductive particles, 6...substrate, 7...laminate, 8...adhesive film piece, 8a...outline, 10...circuit connection structure, 12...circuit electrode (first electrode), 13...first circuit member, 15...bump electrode (second electrode), 16...second circuit member.
Claims
1. An adhesive composition comprising a radically polymerizable compound, a radical polymerization initiator, and an acrylic resin having at least one epoxy group in the molecule and a weight average molecular weight of 5,000 or more.
2. The adhesive composition according to claim 1, wherein the content of the acrylic resin is 1 to 15 mass % based on the total amount of solids contained in the adhesive composition.
3. 2. The adhesive composition according to claim 1, wherein the acrylic resin has an epoxy equivalent of 1,000 or less.
4. The adhesive composition according to claim 1 , wherein the radically polymerizable compound comprises a (meth)acrylate compound having at least one phosphoric acid group in the molecule.
5. 2. The adhesive composition according to claim 1, further comprising at least one thermoplastic resin selected from the group consisting of a phenoxy resin, a polyester resin, a polyurethane resin, a polyester urethane resin, a butyral resin, an acrylic resin, and a polyimide resin.
6. The adhesive composition of claim 1 further comprising conductive particles.
7. An adhesive film comprising a first adhesive layer comprising the adhesive composition according to any one of claims 1 to 6.
8. a second adhesive layer laminated onto the first adhesive layer; The adhesive film of claim 7 , wherein at least one of the first adhesive layer and the second adhesive layer contains conductive particles.
9. A laminate comprising a substrate and the adhesive film according to claim 7 disposed on the substrate.
10. A half-cutting step of cutting the adhesive film of the laminate according to claim 9 along an outline of an outer shape of an adhesive film piece; a step of peeling off the adhesive film piece formed by the half-cutting step from the substrate; a step of interposing the adhesive film piece between a first circuit member having a first electrode and a second circuit member having a second electrode, and thermocompressing the first circuit member and the second circuit member to electrically connect the first electrode and the second electrode to each other.
Citation Information
Patent Citations
Anisotropic conductive adhesive sheet and coupling structure
WO2005054388A1